ECONOMIC RESTRUCTURING: AN IMPERATIVE FOR DIVERSIFICATION OF THE NIGERIAN ECONOMY - Okonkwo, Osmond N; Sunday, Kalu A; Nwosu, Chinedu A (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2019)
Economic diversification is an essentially necessary option to overcoming pending dangers of mono-culture practice. As a mono-culture economy, Nigeria is susceptible to the vicissitude of market forces, because if the single product of the economy is no longer viable, or no more valuable to consolidated consumers, the single-product economy is at threat of recession (fall in gross domestic product). Unfortunately, the Nigeria political economy has been structured to have heavily centralized its economic resources making it impossible for active economic participation of interest groups (including professionals). Where the Federal government has more than 50 percent of accrued revenue, there is obviously no incentive to devolve economic resource control, so long as crude oil continues to provide the needed revenue. This study adopted the political economy methodology. Findings of the study revealed that devolution of economic resources (economic restructuring) is a sine qua non for diversification of the Nigerian economy for sustainable growth and development.